Emergence of quantum correlations from interacting fibre-cavity polaritons - Muñoz-Matutano, Guillermo; Wood, Andrew; Johnsson, Mattias; Vidal, Xavier; Baragiola, Ben Q.; Reinhard, Andreas; Lemaître, Aristide; Bloch, Jacqueline; Amo, Alberto; Nogues, Gilles; Besga, Benjamin; Richard, Maxime; et al. (Nature materials, 2019)
Over the past decade, exciton-polaritons in semiconductor microcavities have revealed themselves as one of the richest realizations of a light-based quantum fluid 1 , subject to fascinating new physics and potential applications 2 – 6 . For instance, in the regime of large two-body interactions, polaritons can be used to manipulate the quantum properties of a light field 7 – 9 . In this work, we report on the emergence of quantum correlations in laser light transmitted through a fibre-cavity polariton system. We observe a dispersive shape of the autocorrelation function around the polariton resonance that indicates the onset of this regime. The weak amplitude of these correlations indicates a state that still remains far from a low-photon-number state. Nonetheless, given the underlying physical mechanism 7 , our work opens up the prospect of eventually using polaritons to turn laser light into single photons. Two-photon correlation measurements in a resonantly excited fibre-cavity polariton system stay below the classical limit for zero time delay, suggesting quantum correlations between the polaritons.